2014
DOI: 10.1097/mao.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

Intracochlear Inflammatory Response to Cochlear Implant Electrodes in Humans

Abstract: Hypothesis This study evaluates the types and degree of tissue response adjacent to the electrode of multichannel cochlear implants. Background cochlear implant electrodes have been classified as biocompatible prostheses. Nevertheless, in some reports, electrode extrusion, chronic inflammation and even soft failure of the implant system have been attributed to a tissue response to the electrode. Methods All celloidin embedded temporal bones with multichannel cochlear implants from the temporal bone collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 37 publications
10
116
0
5
Order By: Relevance
“…The observed histopathology did not offer a morphologic reason for this decrement. The histopathological findings in the implanted ear were similar to those of previous reports in other causes of deafness (21,22).…”
Section: Discussionsupporting
confidence: 89%
“…The observed histopathology did not offer a morphologic reason for this decrement. The histopathological findings in the implanted ear were similar to those of previous reports in other causes of deafness (21,22).…”
Section: Discussionsupporting
confidence: 89%
“…The present histological evaluation focused on the inflammatory response and TNF-alpha positive staining in the inferior cochlear turn after electrode insertion. The formation of fibrosis and bony tissue around the electrode postoperatively was consistent with previous temporal bone studies (Huang et al, 2007;Somdas et al, 2007;Seyyedi et al, 2014). The present study did not find significant differences in the area of new fibrous tissue between the control group and the DEXA group, likely because of the limited number of sections that were evaluated (five H&E-stained sections containing the modiolus).…”
Section: Efficacy Of Glucocorticoid Treatment and Comparisons With Prsupporting
confidence: 90%
“…The causes for this chronic local inflammation might be a delayed hypersensitivity or a local tissue reaction to the CI electrode array (Beruleit et al, 1999; Ho et al, 2003; Puri et al, 2005; Kunda et al, 2006; Nadol et al, 2008; Lim et al, 2011; Neilan et al, 2012; Bennatti et al, 2013). Several temporal bone studies have demonstrated fibrosis and new bone formation adjacent to the electrode track (Nadol and Eddington, 2004; li et al, 2007; Somdas et al, 2007; Seyyedi and Nadol, 2014; Kamakura and Nadol, 2016), and have shown that this local inflammatory response is quite common. (Nadol and Eddington, 2004; Seyyedi and Nadol, 2014; Kamakura and Nadol, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several temporal bone studies have demonstrated fibrosis and new bone formation adjacent to the electrode track (Nadol and Eddington, 2004; li et al, 2007; Somdas et al, 2007; Seyyedi and Nadol, 2014; Kamakura and Nadol, 2016), and have shown that this local inflammatory response is quite common. (Nadol and Eddington, 2004; Seyyedi and Nadol, 2014; Kamakura and Nadol, 2016). Seyyedi and Nadol (2014) demonstrated evidence of a chronic inflammatory reaction including inflammatory mediator cells, fibrous tissue and new bone formation in twenty-eight specimens (100%), from patients who during life underwent cochlear implantation.…”
Section: Introductionmentioning
confidence: 99%